Optimización de la capacidad volumétrica del actual sistema de vertimiento en campo Rubiales incrementándola a trescientos mil barriles de agua por día. (2021)
The loss of volumetric capacity in the dumping system represents the waste of fluid treatment capacity, which translates into loss of production. In this project, a hydraulic analysis was carried out, based on the design and operational information of the Campo Rubiales dumping system, through the construction of 3 different simulation cases (Ideal Case, Pump Test Representation Case and Current Case). From the comparison of the design properties such as the factor “C” between the cases, the pressure profiles obtained and the comparison of pressure and flow in the distribution head towards the discharge branches C, D and E, it was obtained As a result, the difference in pressure readings at this point between the Pump Test Representation Case and the actual test data was 28 Psig in a system with a common “C” factor for pipes in good condition.